Callous-unemotional behaviors and conduct problems in Chinese preschoolers: the moderating roles of surgency and gender - Zhu, Jingjing; Shu, Xin; Li, Zhuyi; Li, Yan (Frontiers in Psychology, 2024)
Conduct problems in children are related to callous-unemotional (CU) behaviors. However, results of the relationships between CU behaviors and conduct problems among preschoolers mainly focused on Western countries, no studies have examined whether CU behaviors predict conduct problem in Chinese preschoolers. The primary objective of the current study therefore was to examine the associations between CU behaviors and conduct problems as well as the moderating effects of surgency and child gender in Chinese preschool children. The present study randomly selected 2154 children (1043 boys, Mage = 56 months, SD = 10.47) from six kindergartens in Shanghai, People's Republic of China. Mothers rated children's surgency and teachers reported children's CU behaviors and conduct problems. Results demonstrated that CU behaviors were positively associated with conduct problems. Surgency and child gender significantly moderated these associations. Specifically, CU behaviors were positively associated with conduct problems, with a stronger effect found for high levels of surgency. CU behaviors had a positive association with conduct problems, with a stronger effect found for boys. The current findings indicate that temperament and gender characteristics influence conduct problems in preschoolers who exhibit high levels of CU behaviors.